Pembangunan Sistem Pengolahan Data Absensi Karyawan Menggunakan Fingerprint - Amuharnis, Amuharnis (Jurnal EDik Informatika, 2014)
This research aims to study and analyze employee absent system using fingerprint at Bung Hatta University, in addition, this study also to provide the best solution in the absence of data processing, calculation of attendance data, making and presenting the summary report of employees absent. This study conduct phase analysis of the data collected by the system design tool and then designed the input design, output design, file design and the program flow of the existing system. The results of this research applied into an application program using the programming language PHP and a MySQL database as a permanent storage medium, and from this research will produce absent information system using fingerprint at Badan Kepegawaian Bung Hatta University. Keywords: Information System, Employee Absent, Finger Print